THE DIMENSIONS OF JUDICIAL PROFESSION IN LITHUANIA: QALIFICATION, COMPETENCE, AND PERSONAL QUALITIES - Navickienė, Žaneta; Žiemelis, Darius (Teisė, 2016)
The article argues that judicial profession is multi-dimensional, and is constituted of at leats three components, i.e., formal qualification, constant training, and personal qualities that arise from one’s inner determination to see the profession as a calling. Three parts of this article have been dedicated to grounding that claim. The first part analyses the judicial qualification and judicial training peculiarities. The second part analyses judicial training in terms of its content and form and highlights its strengths and areas for improvement. Finally, the third part distinguishes the personal qualities that allow the judge to make impartial decisions, based on Max Weber’s ideal types of political leadership. The research showed that professional requirements for the judges are clearly defined in legal acts that provide a strong link between the judge’s professional requirements and continuous development of competence. The current Lithuanian judicial training system is made of two parts (i.e., the basic and additional training) that allow a consistent and systematic segmentation of the key and professional competences crucial for the judge’s activities. This allows the judge to both develop the competences essential in his or her activities and discretely develop his or her competence in the fields he or she finds it necessary. In terms of their form, judicial training programmes are defined under clear methodological guidelines, although some other important guidelines, such as objectives, goals and expectations, should be included. In terms of their content, the programmes are thorough, targeted to specific groups, and featuring continuous competence development. However, due to constant social, cultural and legal regulatory framework changes, they should be regularly updated. The judges’ impartiality in making lawful rulings arises not only from such sociology-wise universal ideas as good faith, devotion to one’s duty and independent decision making, the personal qualities common to the members of various occupational categories. A very important condition to judicial professionalism is one’s determination to see one’s activities as a call for dispensing justice. This leads to passion (devotion) for the cause of justice, and responsible administration of justice and as well as maintaining a proper distance between one’s personal opinions and beliefs and the participants of proceedings.